SPATIAL PATTERN OF KARST ROCK DESERTIFICATION IN THE MIDDLE OF GUIZHOU PROVINCE, SOUTHWESTERN CHINA - Huang Q.; Cai Yu. (My University, 2007)
Karst rocky desertification is a typical type of land degradation in the Southwestern China. It has great ecological and economical implications for the local people. Landsat images from the middle of Guizhou Province collected in 1974, 1993 and 2001 were used for change detection of the pattern of Karst rocky desertification. The results show the following findings: (1) Desertification area expanded drastically in 27 years, at an increasing rate about 116.2 km2/year. (2) High areas (900–1,500 m) are the most affected. (3) Areas with the slope <5° or >25° are also easily tend to be Karst rocky deserted. (4) The process of Karst rocky desertification is nearly irreversible. Few areas of Karst rocky desertification could be meliorated to non-desertification land. (5) Most of the degraded lands are located in the south and the central of the study region, and the meliorated land areas are sparsely located in the east and the west part of the region. All these findings would provide bases for the decision-making of the local government to improve the Karst rocky desertification
Keywords: LAND DEGRADATION; KARST ROCKY DESERTIFICATION; TEMPORAL-SPATIAL PATTERN; SOUTHWESTERN CHINA